O-026 Prior antiplatelet use and thrombectomy outcomes. (23rd July 2017) - Pandhi,; Krishnan, R; Dillard, K; Ishfaq, M; Singh, S; Hoit, D; Arthur, A; Tsivgoulis, G; Alexandrov, A; Elijovich, L; Goyal, N
Abstract : Background: Multiple recent studies and randomized controlled trails have advocated mechanical thrombectomy (MT) as a front line management for emergent large vessel occlusion (ELVO) strokes. There is very limited information as to how prior use of antiplatelet (APT) drug affects the outcomes in these patients. In this study we sought to evaluate the association of prior use of APT drug and outcomes after MT in ELVO patients. Methods: Consecutive patients with ELVO treated with MT during a 3 year period were evaluated. ELVO patients identified as being on any antiplatelet drugs versus not on any prior to MT. Standard safety (symptomatic intracerebral hemorrhage (SICH) and effectiveness outcomes [complete recanalization, time to recanalization, and favorable outcome (defined as mRS of 0–2 at 3 months)] were compared in both groups. Complete recanalization was defined as TICI score of 2b or 3. Results: We evaluated 217 consecutive ELVO patients (mean age 62±18, male 49.8% and median NIHSS 16 (IQR 12–21) who underwent MT. A total of 146 patients (67.3%) were not on prior anti platelets. Prior use of APT medications was reported in 71 patients [aspirin: 56 patients (25.8%], Plavix: 2 patients (1%), Aspirin and Plavix: 12 patients (5.5%) and Aggrenox: 1 patient (0.5%)]. The ELVO group with prior use of APT medication had higher rates of successful recanalization [79% vs 63%, p=0.028] compared to the group without prior APT use. The ELVO group with prior APT use did not differ significantly in terms of groin puncture to recanalization time [minute, median (IQR); 51 (32–67) vs 48 (38–80), p=0.390], rates of favorable outcome [OR: 1.41, 95% CI: (0.63–3.15), p=0.403], and rates of sICH (p>0.1) compared to the group without prior APT use. In multivariable analyses, prior use of APT drug was independently associated with higher rates of successful recanalization (OR: 2.40; 95% CI (1.06–5.46), p=0.036) after adjusting for potential confounders. Further subgroup analyses on ELVO patients with prior use of single vs dual APT drug did not show any difference in safety or efficacy outcomes (p>0.0.1) Conclusion: Prior use of APT drug is associated with higher rates of successful recanalization in ELVO patients after MT, however no difference in rates of sICH or functional outcome was noted. Larger studies are needed to further evaluate the role of prior treatment with APT drug in ELVO patients treated with MT. Disclosures: A. Pandhi: None. R. Krishnan: None. K. Dillard: None. M. Ishfaq: None. S. Singh: None. D. Hoit: None. A. Arthur: None. G. Tsivgoulis: None. A. Alexandrov: None. L. Elijovich: None. N. Goyal: None.